The Prevalence of Social Withdrawal in Infants With Cleft Lip and Palate: The Feasibility of the Full and the Modified Versions of the Alarm Distress Baby Scale - Pérez Martínez, Carla; Grollemund, Bruno; Gavelle, Pascale; Viaux-Savelon, Sylvie; Guedeney, Antoine (Frontiers in Pediatrics, 2022)
Background Social withdrawal is a risk indicator for infant development with both organic and nonorganic causes. Cleft lip and palate (CLP) impose a higher risk of physical and emotional distress in infants and alters parent-infant relationships. The ADBB scale is a screening tool to identify social withdrawal as a sign of distress in infants. The aim of this study is to evaluate the prevalence of social withdrawal behavior in infants with CLP using the full 8-item ADBB scale and the modified 5-item ADBB scale, and to examine the feasibility of both scales. Methods 145 infants with Cleft Lip and Palate were enrolled and video recorded during a pediatric consultation. All infants were scored by two expert raters trained in ADBB scale, and subsequently scored with the m-ADBB by an independent expert. We measured the interrater agreement for the full ADBB scale and psychometric properties of both scales. Results The full ADBB scale identified 15.9% of infants as having social withdrawal behavior (score above cutoff ≥5). Among the infants evaluated with the m-ADBB scale, 44.9% had a score above the suggested cutoff (≥2). For both scales, the item “vocalization” showed the higher scores. We found a good internal consistency for the full ADBB (Cronbach’s alpha=.82) and an acceptable internal consistency for the modified ADBB (Cronbach’s alpha=.71) The interrater agreement for the full ADBB scale was excellent (kappa=.837). The Spearman correlation coefficient between the total scores of the two versions was 0.88 (P < 0.001). Conclusion Our results indicate a relatively high prevalence of social withdrawal in infants with Cleft Lip and Palate, especially evaluated with the modified 5-item ADBB scale. We found that the full ADBB and the modified ADBB scales are feasible to use as screening tools of social withdrawal in this population.